The Poetic Works of Helius Eobanus Hessus : Volume 7: Notes to Volume 6: The Fruits of Autumn - Vredeveld, Harry, (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
Volume 7 is a companion to the preceding volume, "The Fruits of Autumn." As such, it offers a rich trove of explanatory and philological notes on all the poetic texts presented there. Headnotes to individual sections provide information on meter and, as needed, on genre, tradition, historical and personal background, as well as on earlier editions, translations, and interpretations. A special focus is the documentation of ancient, medieval, and early modern sources and textual parallels (similia). A List of Abbreviations, Index of Medieval and Renaissance Words, Glossarial Index, and General Index round out this volume.